Internet as a Resource of Learning in Increasing Students` Learning Outcomes on Social Studies Subject - Ginting, Febriana Br (International Journal Pedagogy of Social Studies, 2019)
This research was conducted based on students’ diverse learning outcomes. To maximize learning outcomes, a supportive learning resource is needed. 8th grader students of Junior High School 12 Bandung have used the internet in social science subject learning. Given the limitations of school facilities and infrastructure, all students access the internet in social science subject learning using personal data connection. The internet is used by teachers and students in finding learning materials and seeking completion of school assignments. The internet helps students to get up to date and relevant learning resources. The method used for collecting the data in this study was through observation, interview, and documentation. The research target was students. The findings of this study indicated that by using the internet, students are easier to find learning material and it helps them to work on school assignments completion, and it helps them to obtain scores that tend to increase. The use of the internet as a learning resource makes students better understand the subject matter, makes it easier to find learning material as well as to find answers for their assignments. However, the barrier to the use of the internet as a source of learning for students was when the learning materials sought are combined with other learning materials.